PENGARUH CAMPURAN BAHAN BAKAR PERTALITE DAN PERTAMAX TERHADAP NILAI TORSI, DAYA DAN EMISI GAS BUANG SEPEDA MOTOR 150CC: PENGARUH CAMPURAN BAHAN BAKAR PERTALITE DAN PERTAMAX - hajar isworo; Kurnia Dwi Artika; Rusuminto Syahyuniar; Anggun Angkasa Bela Persada; Yulima Melsi Lingga; Imron Musthofa; Adhiela Noer Syaief; Rendy Bagus Kurniawan (POLITALA PRESS, 2022)
The problem that occurs today is that many fuel injection vehicles that use Pertamax are switching to Pertalite for economic reasons. This study aims to determine the difference between the use of pure fuel and a mixture of Pertamax and Pertalite fuels on the power, torque and exhaust emissions produced. This study uses the method of collecting data from pure fuel and combining fuel mixtures from 100% Pertamax, 100% Pertalite and 90% Pertamax 10% Pertalite, 80% Pertamax 20% Pertalite, 70% Pertamax 30% Pertalite The result, the highest torque is at Pertamax 100% 12.34 N.m and Max Power 14.15 Hp. The exhaust gas emission content of pure Pertamax is lower, namely CO 15.3%, HC 458 ppm, CO2 8.4%, and O2 5.95%.